AN ANALYSIS OF FIGURATIVE LANGUAGE IN ORIAH MOUNTAIN DREAMER"™S POEMS - Hernanda, Anugrah Tri; Supardi, Iwan; Suhartono, Luwandi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2024)
This research journal delves into a thorough examination of the figurative language embedded within the poem "The Invitation," penned by Oriah Mountain Dreamer. Through meticulous scrutiny of metaphorical constructs, similes, personification, symbolism, alliteration, and repetition, the study endeavors to unveil the multifaceted layers of meaning and emotional resonance encapsulated within the poem's verses. By meticulously dissecting the poet's adept manipulation of language, the research aims to shed light on the profound thematic explorations of self-discovery, authenticity, and human connection that reverberate throughout Dreamer's work. "The Invitation" emerges as a testament to Dreamer's artistic vision and her skillful employment of figurative language to evoke visceral responses and provoke introspection among readers. This comprehensive analysis not only underscores the inherent beauty of the poem but also underscores the significance of figurative language in enhancing its aesthetic and emotional appeal. Through an exhaustive investigation, this research journal seeks to provide a nuanced understanding of how the strategic implementation of figurative language enriches the poetic experience, thus contributing to the broader discourse on the interplay between language, meaning, and artistic expression in poetry.